Effect of boron fertilisation on the flavour of carrots - Applicability of organoleptic analyses to carrots - Némethy-Uzoni, H.; Kókai, Z. (International Journal of Horticultural Science, 2003)
Foliar boron fertilisation has had positive influence only on carotene content. Results were evaluated with chemical analyses and sensory tests. It has been observed that sensory tests are able to detect bitter flavour and also to measure its interaction with sweet flavour. Sensory tests for evaluation are generally used in the EU, also in the case of fruits and vegetables. With the aid of students and staff having received training and acquired practice, our University has the possibility to complete chemical analyses in such a way that satisfies modern demands, as well as facilitating the sale of the products on foreign markets.